Low-Frequency NNRTI-Resistant HIV-1 Variants and Relationship to Mutational Load in Antiretroviral-Naïve Subjects - Gupta, Shaili (MDPI, 2014)
Low-frequency HIV variants possessing resistance mutations against non‑nucleoside reverse transcriptase inhibitors (NNRTI), especially at HIV reverse transcriptase (RT) amino acid (aa) positions K103 and Y181, have been shown to adversely affect treatment response. Therapeutic failure correlates with both the mutant viral variant frequency and the mutational load. We determined the prevalence of NNRTI resistance mutations at several RT aa positions in viruses from 204 antiretroviral (ARV)-naïve HIV-infected individuals using deep sequencing, and examined the relationship between mutant variant frequency and mutational load for those variants. Deep sequencing to ≥0.4% levels found variants with major NNRTI-resistance mutations having a Stanford-HIVdb algorithm value ≥30 for efavirenz and/or nevirapine in 52/204 (25.5%) ARV-naïve HIV-infected persons. Eighteen different major NNRTI mutations were identified at 11 different positions, with the majority of variants being at frequency >1%. The frequency of these variants correlated strongly with the mutational load, but this correlation weakened at low frequencies. Deep sequencing detected additional major NNRTI-resistant viral variants in treatment-naïve HIV-infected individuals. Our study suggests the significance of screening for mutations at all RT aa positions (in addition to K103 and Y181) to estimate the true burden of pre-treatment NNRTI-resistance. An important finding was that variants at low frequency had a wide range of mutational loads (>100-fold) suggesting that frequency alone may underestimate the impact of specific NNRTI-resistant variants. We recommend further evaluation of all low-frequency NNRTI-drug resistant variants with special attention given to the impact of mutational loads of these variants on treatment outcomes.